2016
DOI: 10.1515/plm-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro effect of antimicrobial photodynamic therapy with methylene blue in two different genera of dermatophyte fungi

Abstract: Esta obra, editada por José María Infante Bonfiglio y María Eugenia Flores Treviño, recoge doce trabajos de investigación presentados en el VI Coloquio Internacional del Programa EDICE (Estudios sobre el Discurso de la Cortesía en Español), celebrado en 2011 en Monterrey (México). Dichos trabajos aparecen organizados en tres partes, dedicadas respectivamente a estudios sobre imagen y (des)cortesía, actos de habla y (des)cortesía y atenuación.Los autores cuyas investigaciones integran este libro asumen que la (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Spezzia‐Mazzocco et al. have demonstrated that PDT with MB is an effective inhibitor of Trichophyton strains in vitro and Souza et al. have provided evidence that PDT with MB is effective at treating onychomycosis caused by T. rubrum in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Spezzia‐Mazzocco et al. have demonstrated that PDT with MB is an effective inhibitor of Trichophyton strains in vitro and Souza et al. have provided evidence that PDT with MB is effective at treating onychomycosis caused by T. rubrum in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In turn, use of photodynamic therapy at doses of energy equal to 3 and 12 J/cm 2 is not effective in growth inhibition of T. rubrum isolates [32]. Speezia-Mazzocco et al [48] showed in vitro greater than 50% growth inhibition rate of dermatophyte classified in Trichophyton genera after using methylene blue photodynamic therapy with energy doses higher than 20 J/cm 2 . In addition, used by them repetitive exposures to energy doses equal to 20 J/ cm 2 with 20 μM of methylene blue to achieve 97% growth inhibition in case of T. tonsurans strains [48].…”
Section: Discussionmentioning
confidence: 99%
“…Speezia-Mazzocco et al [48] showed in vitro greater than 50% growth inhibition rate of dermatophyte classified in Trichophyton genera after using methylene blue photodynamic therapy with energy doses higher than 20 J/cm 2 . In addition, used by them repetitive exposures to energy doses equal to 20 J/ cm 2 with 20 μM of methylene blue to achieve 97% growth inhibition in case of T. tonsurans strains [48]. Guffey et al [32] note that not only energy density but also optical intensity is an important parameter in photodynamic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Against this background, Spezzia-Mazzocco et al [21] report on the in-vitro effect of antimicrobial photodynamic therapy (aPDT) with methylene blue (MB) in six dermatophyte fungi of the Trichophyton and Microsporum genera that present a health risk, including a new fungus (T. tonsurans) that has been never treated before with MB in vitro. It was shown that MB is an effective PS to inhibit fungal growth through aPDT, reaching a complete inhibition for most of the fungi tested.…”
Section: Light and Lasers On Fungal Infectious Diseasesmentioning
confidence: 99%